Lithium disilicate glass ceramic containing zinc spinel as sub-crystalline phase, and preparation method and product thereof
By introducing ZnO and Al2O3 into lithium disilicate glass ceramics, the zinc spinel secondary crystal phase is formed, which solves the problem of insufficient strength and fracture toughness of lithium disilicate glass ceramics, and significantly improves its mechanical properties and acid- and alkali-resistant properties. , extends service life and widens indications.
Patent Information
- Application Number
- CN202411712369.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-21
AI Technical Summary
In dental clinical restoration, lithium disilicate glass ceramics are prone to collapse and cracking due to insufficient strength and fracture toughness. The types of indications are limited and are easily corroded in acid and alkali environments, which affects the service life.
By introducing ZnO and Al2O3 into the base glass components during the glass melting stage, zinc spinel is formed as a secondary crystal phase, thereby improving the strength, fracture toughness and acid-base corrosion resistance of lithium disilicate glass ceramics.
It significantly improves the strength and fracture toughness of lithium disilicate glass ceramics, reduces the phenomenon of ceramic collapse and cracking during processing and use, extends the service life of the restoration, and broadens its indication types.
Smart Images

Figure CN119490305A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium disilicate glass ceramics, and in particular relates to a lithium disilicate glass ceramic containing zinc spinel as a secondary crystalline phase and a preparation method and product thereof. Background Art
[0002] In the field of dental clinical restoration, lithium disilicate glass ceramics occupy a certain market share. Although its aesthetic effect is good, it is far less than the market share of zirconium oxide ceramics. The reason is that its strength and fracture toughness are quite different from those of zirconium oxide. In the process of clinical application, it is easy to have phenomena such as porcelain collapse and cracking. In addition, the types of indications are limited. It is not suitable for use as posterior molar crowns and functional dental bridges, which have high requirements for strength and fracture toughness. This affects its scope of use, customer experience and the service life of the restoration. In addition, the human oral environment is basically weakly acidic, and we often eat some acidic and alkaline foods, which will cause acid and alkali corrosion to the restoration over a long period of time, affecting the performance and service life of the restoration. Summary of the invention
[0003] The present invention provides a lithium disilicate glass ceramic containing zinc spinel as a secondary crystalline phase, a preparation method and a product thereof. The zinc spinel secondary crystalline phase precipitated in the lithium disilicate glass ceramic can improve the strength, increase the fracture toughness and improve the ability of the lithium disilicate glass ceramic to resist acid and alkali corrosion, and can make the restoration less likely to cause ceramic chipping and cracking during processing, polishing and use, thereby improving product stability and broadening the application space of the product.
[0004] The present invention describes a lithium disilicate glass ceramic containing galvanneal as a secondary crystalline phase. In order to achieve the above-mentioned purpose, the present invention provides a lithium disilicate glass ceramic containing galvanneal as a secondary crystalline phase. The glass ceramic is prepared by simultaneously introducing ZnO and Al2O3 components necessary for forming the galvanneal secondary crystalline phase into the basic glass component during the glass melting stage, melting the glass in an air atmosphere, and adopting a casting method or a sintering method. In the obtained product, galvanneal is precipitated as a secondary crystalline phase in the main crystalline phase lithium silicate glass ceramic.
[0005] Preferably, the basic glass component includes the following components in percentage by mass:
[0006]
[0007] In the above scheme, the content of ZnO and Al2O3 is crucial because it involves the basis for the precipitation of the optimal ratio of lithium disilicate crystals and zinc spinel crystals. Specifically, when the content of ZnO and Al2O3 is high, it is easier to precipitate zinc spinel crystals, which can fill the gaps of lithium disilicate crystals well to make its structure more compact. However, when zinc spinel crystals are precipitated excessively, the originally dense structure will become loose, which will lead to a decrease in strength and fracture toughness. Therefore, coordinating the content of each component in the formula is the key to ensuring the precipitation of a good number of lithium disilicate crystals and zinc spinel crystals.
[0008] Preferably, the basic glass component further comprises a compound containing Tb ions, and its content is 0.2-0.5%, preferably 0.3-0.4%, calculated as a percentage by mass of Tb4O7.
[0009] Preferably, the additive is further included, wherein the additive is selected from at least one of alkaline earth metal oxides, trivalent element oxides, tetravalent element oxides, pentavalent element oxides and hexavalent element oxides, and the content of the additive is 0-12wt%;
[0010] The alkaline earth metal oxide is selected from at least one of CaO, BaO, MgO, SrO or a mixture thereof; the oxide of the trivalent element is other than Al2O3 and is selected from at least one of B2O3, Y2O3, La2O3, Bi2O3 or a mixture thereof; the oxide of the tetravalent element is other than SiO2, ZrO2, TiO2 and is selected from at least one of SnO2, TiO2 and GeO2; the oxide of the pentavalent element is selected from at least one of P2O5 and Nb2O5; the oxide of the hexavalent element is selected from at least one of WO3 and MoO3.
[0011] Preferably, it further comprises a colorant, wherein the colorant is selected from at least one of a yellow colorant, a red colorant, and a gray colorant, and the content thereof is 0-5.5wt%, preferably 0.5-3.5%;
[0012] The yellow colorant is selected from at least one of CeO2, Pr2O3, and V2O5; the red colorant is Er2O3; and the gray colorant is selected from at least one of MnO, NiO, and Nd2O3.
[0013] Preferably, it further comprises a fluorescent agent, wherein the fluorescent agent comprises at least one of oxides, carbonates, nitrates and phosphates of at least two of the following elements Sm, Dy, Er, Yb, Nd, Tm and Eu, and the content thereof is 0.1-3 wt%, preferably 0.2-1.5% wt%;
[0014] The base glass component also includes no more than 0.01 wt % of Fe ions.
[0015] The present invention also provides a method for preparing the lithium disilicate glass ceramic according to any one of the above technical solutions, comprising the following steps:
[0016] According to the formula, basic glass components, additives, colorants and fluorescent agents are selected and mixed evenly, melted and water quenched in an air atmosphere, the quenched glass frit is melted again, and the melted glass liquid is poured into the required mold for molding and heat treatment.
[0017] Preferably, the melting temperature is 1450°C-1650°C, and the holding time is 60-120min; it is understandable that after the carbonate, oxide and other raw materials are fully mixed and evenly, they can be melted at this temperature to form lithium silicate glass, and then poured into water and quickly cooled to form a glass frit.
[0018] Preferably, the remelting temperature is 1450°C-1650°C, and the holding time is 60-120min;
[0019] The heat treatment temperature is 500-1100°C, preferably 600-1000°C.
[0020] In the above scheme, the regulation of sintering temperature and time is the key to precipitating lithium disilicate crystals and zinc spinel crystals of a certain proportion and shape. Among them, the precipitated lithium disilicate is a rod-shaped crystal, and the zinc spinel is a spherical crystal (the crystal content is less than 50%), and the two crystals fill each other. Specifically, when the sintering temperature is low and the time is short, the precipitated crystals are smaller and less, the glass matrix is more, the light transmittance is better, and the corresponding mechanical properties such as strength and fracture toughness will decrease. When the sintering temperature is high and the time is long, the precipitated crystals are larger and more, and the light transmittance is lower. When the crystals are too large, the lithium disilicate crystals and zinc spinel crystals cannot fill the entire space well, which will also reduce the density of the product, thereby affecting the mechanical properties such as strength and fracture toughness. In addition, when mixing the raw materials, the powders of each component need to be mixed evenly, so that the glass components will be more uniform after water quenching. During the glass melting process, the glass liquid should also be mixed as evenly as possible. It is best to have a stirring step during the period, so that lithium disilicate crystals and zinc spinel crystals can be evenly precipitated, thereby improving the density and stability of the product.
[0021] It is understood that the press ceramic blocks prepared by the above method can be used for restorations made by hot die casting, and the CAD ceramic blocks can be processed into restorations using CAD / CAM technology, with or without crystallization treatment. If crystallization treatment is used, the treatment temperature is 600-1000°C.
[0022] The present invention also provides a method for preparing the lithium disilicate glass ceramic according to any one of the above technical solutions, comprising the following steps:
[0023] According to the formula, basic glass components, additives, colorants and fluorescent agents are selected and mixed evenly, melted and water quenched in an air atmosphere, the water-quenched glass frit is ground into glass powder, and then the glass powder is placed in a mold for pressing and forming, and is obtained after heat treatment.
[0024] Preferably, a colorant and / or a mixed glass powder with transparency is added to the glass powder as a layer of common powder, which is then put into a mold for pressing.
[0025] Preferably, at least three layers of common powder are added. It is understandable that, by using this solution, lithium silicate glass or lithium silicate glass ceramic with multiple layers of color and / or transparency can be prepared, thereby preparing a restoration that can achieve a gradual lightening of color and a gradual increase in transparency from the neck to the cutting end.
[0026] Preferably, the melting temperature is 1450°C-1650°C, and the holding time is 60-120min;
[0027] The average particle size of the ground powder is 1-100um, preferably 2-20um;
[0028] During pressing, dry pressing is adopted with a molding pressure of 100-260MPa, or dry pressing is first performed with a pressure of 15-100MPa, and then isostatic pressing is performed with a pressure of 100-260MPa;
[0029] The sintering temperature is 350-1200°C, preferably 450-1000°C;
[0030] The vacuum degree is controlled at 100-5000Pa, preferably 500-3000Pa.
[0031] The present invention also provides a dental restoration prepared by using the lithium disilicate glass ceramics described in any one of the above technical solutions.
[0032] As a preferred method, compared with the conventional lithium disilicate glass ceramics for preparing dental restorations, the strength reaches above 498MPa and the fracture toughness reaches 1.9MPa·m 1 / 2 above.
[0033] Compared with the prior art, the advantages and positive effects of the present invention are:
[0034] 1. The lithium disilicate glass ceramics provided by the present invention precipitate zinc spinel as a secondary crystalline phase, the melting process does not require a special atmosphere, the process is simple, the effect is stable, and it is easy to mass produce. The zinc spinel secondary crystalline phase can improve the strength, fracture toughness and acid and alkali corrosion resistance of lithium disilicate glass ceramics. It is not easy to produce ceramic collapse and cracking during use, thereby improving product stability and broadening the product application space.
[0035] 2. The precipitated zinc spinel not only has the advantages of spinel such as excellent dielectric properties and good thermal stability, but also has better acid and alkali corrosion resistance than magnesium aluminum spinel and iron aluminum spinel. Its application in dentistry can improve the use tolerance of denture glass ceramic products, increase the success rate of restorations, and extend the service life of restorations. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 XRD test pattern of the sample prepared by the formula of Example 1;
[0037] Figure 2 XRD test pattern of the sample prepared by the formula of Example 2;
[0038] Figure 3 XRD test pattern of the sample prepared by the formula of Example 3;
[0039] Figure 4 XRD test pattern of the sample prepared by the formula of Example 4;
[0040] Figure 5 This is the XRD test pattern of the sample made according to the recipe of Example 5. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Example 1 (melting press)
[0043] According to the component contents shown in Table 1 below, take the raw material components of the basic glass, and each raw material can be selected from its oxide, carbonate or phosphate, etc., and mix them thoroughly; put the mixed raw materials into a platinum crucible, put the platinum crucible into a furnace for melting, control the melting temperature to 1550°C, and the melting time to 60 minutes, so that the glass liquid is homogenized, and then poured into cold water to obtain a glass frit; the glass frit is melted at 1500°C for 60 minutes, and then cast into a mold for molding, and the ceramic block is crystallized at 830°C in a box furnace for 2 hours to obtain a press ceramic block. The obtained press ceramic block can be used to prepare a lithium disilicate glass ceramic restoration through a hot die casting process.
[0044] Table 1
[0045]
[0046]
[0047] The samples prepared by the formula of Example 1 were subjected to XRD test. Figure 1 As shown, the sample contains three kinds of crystals: Li2Si2O5, Li2Si3O5 and ZnAl2O4. Among them, the peak of Li2Si2O5 crystal is relatively strong and is the main crystalline phase. It also generates ZnAl2O4 secondary crystalline phase which is not possessed by other similar lithium disilicate glass ceramics.
[0048] Example 2 (Melting CAD Secondary Crystallization)
[0049] According to the component contents shown in Table 2 below, the raw material components of the basic glass are prepared, and each raw material can be selected from its oxide, carbonate or phosphate, etc., and fully mixed; the mixed raw materials are placed in a platinum crucible, and the platinum crucible is placed in a furnace for melting, and the melting temperature is controlled to be 1650°C, and the melting time is 80 minutes, so that the glass liquid is homogenized, and then poured into cold water to obtain a glass frit; the glass frit is then melted at 1450°C for 120 minutes, and then cast into a mold for molding, and the ceramic block is crystallized at 600°C in a box furnace for 2 hours to obtain a CAD ceramic block. The obtained CAD ceramic block is subjected to a CAD / CAM process, and a crystallization treatment at 870°C is required for 1 hour, and a lithium disilicate glass ceramic restoration can be prepared.
[0050] Table 2
[0051]
[0052]
[0053] The samples prepared by the formula of Example 2 were subjected to XRD test. Figure 2As shown, the sample contains three kinds of crystals: Li2Si2O5, Li2Si3O5 and ZnAl2O4. Among them, the peak of Li2Si2O5 crystal is relatively strong and is the main crystalline phase. It also generates ZnAl2O4 secondary crystalline phase which is not possessed by other similar lithium disilicate glass ceramics.
[0054] Example 3 (Melting Method CAD Secondary Crystallization)
[0055] According to the component contents shown in Table 3 below, take the raw material components of the basic glass, and each raw material can be selected from its oxide, carbonate or phosphate, etc., and mix them thoroughly; put the mixed raw materials into a platinum crucible, put the platinum crucible into a furnace for melting, control the melting temperature to 1450°C, and the melting time to 90 minutes, so that the glass liquid is homogenized, and then poured into cold water to obtain a glass frit; the glass frit is then melted at 1600°C for 60 minutes, and then cast into a mold for molding, and the ceramic block is crystallized at 680°C in a box furnace for 2 hours to obtain a CAD ceramic block. The obtained CAD ceramic block is subjected to a CAD / CAM process, and at the same time, it needs to be crystallized at 860°C for 1 hour to prepare a lithium disilicate glass ceramic restoration.
[0056] Table 3
[0057]
[0058]
[0059] The samples prepared by the formula of Example 3 were subjected to XRD test. Figure 3 As shown, the sample contains three kinds of crystals: Li2Si2O5, Li2Si3O5 and ZnAl2O4. Among them, the peak of Li2Si2O5 crystal is relatively strong and is the main crystalline phase. It also generates ZnAl2O4 secondary crystalline phase which is not possessed by other similar lithium disilicate glass ceramics.
[0060] Example 4 (Sintering Press)
[0061] According to the component contents shown in Table 4 below, take the raw material components of the basic glass, and each raw material can be selected from its oxide, carbonate or phosphate, etc., and mix them thoroughly; put the mixed raw materials into a platinum crucible, put the platinum crucible into a furnace for melting, control the melting temperature to 1450°C, and the melting time to 120min, so that the glass liquid is homogenized, and then poured into cold water to obtain a glass frit; the frit is coarsely ground and finely ground to a particle size of D50=5μm, and the ground glass powder is placed in a prepared mold, dry pressed, with a molding pressure of 15MPa, and then isostatically pressed, with a pressure of 260MPa; the blank is sintered in a vacuum atmosphere furnace, sintered at a temperature of 900°C for 1h, and the vacuum degree is controlled at 3000Pa. The obtained press porcelain block can be prepared into a lithium disilicate glass ceramic restoration by a hot die casting process.
[0062] Table 4
[0063]
[0064]
[0065] The samples prepared by the formula of Example 4 were subjected to XRD test. Figure 4 As shown, the sample contains three kinds of crystals: Li2Si2O5, Li2Si3O5 and ZnAl2O4. Among them, the peak of Li2Si2O5 crystal is relatively strong and is the main crystalline phase. It also generates ZnAl2O4 secondary crystalline phase which is not possessed by other similar lithium disilicate glass ceramics.
[0066] Example 5 (Sintering CAD Secondary Crystallization)
[0067] According to the component contents shown in Table 5 below, take the raw material components of the basic glass, and each raw material can be selected from its oxide, carbonate or phosphate, etc., and mix them thoroughly; put the mixed raw materials into a platinum crucible, put the platinum crucible into a furnace for melting, control the melting temperature to 1480°C, and the melting time to 90min, so that the glass liquid is homogenized, and then poured into cold water to obtain a glass frit; the frit is coarsely ground and finely ground to a particle size of D50=2μm, and the ground glass powder is placed in a prepared mold, dry pressed once, and the pressure is 240MPa; the blank is sintered in a vacuum atmosphere furnace at a temperature of 650°C for 2h, and the vacuum degree is controlled at 1600Pa. The obtained CAD ceramic block can be prepared into a blank by CAD / CAM process, and then crystallized at 880°C for 1h to obtain a lithium disilicate glass ceramic restoration.
[0068] Table 5
[0069]
[0070]
[0071] The samples prepared by the formula of Example 5 were subjected to XRD test. Figure 5 As shown, the sample contains three kinds of crystals: Li2Si2O5, Li2Si3O5 and ZnAl2O4. Among them, the peak of Li2Si2O5 crystal is relatively strong and is the main crystalline phase. It also generates ZnAl2O4 secondary crystalline phase which is not possessed by other similar lithium disilicate glass ceramics.
[0072] Example 6 (melting press)
[0073] According to the component contents shown in Table 6 below, take the raw material components of the basic glass, and each raw material can be selected from its oxide, carbonate or phosphate, etc., and mix them thoroughly; put the mixed raw materials into a platinum crucible, put the platinum crucible into a furnace for melting, control the melting temperature to 1630°C, and the melting time to 120min, so that the glass liquid is homogenized, and then poured into cold water to obtain a glass frit; the glass frit is then melted at 1550°C for 80min, and then cast into a mold for forming, and the ceramic block is crystallized at 840°C in a box furnace for 1h to obtain a press ceramic block. The obtained press ceramic block can be used to prepare a lithium disilicate glass ceramic restoration through a hot die casting process.
[0074] Table 6
[0075]
[0076]
[0077] Example 7 (Melting Method CAD Primary Crystallization)
[0078] According to the component contents shown in Table 7 below, the raw material components of the basic glass are prepared, and each raw material can be selected from its oxide, carbonate or phosphate, etc., and fully mixed; the mixed raw materials are placed in a platinum crucible, and the platinum crucible is placed in a furnace for melting, and the melting temperature is controlled to be 1530°C, and the melting time is 120min, so that the glass liquid is homogenized, and then poured into cold water to obtain a glass frit; the glass frit is then melted at 1450°C for 60min, and then cast into a mold for molding, and the ceramic block is crystallized at 830°C in a box furnace for 1h to obtain a CAD ceramic block. The obtained CAD ceramic block can be used to prepare a lithium disilicate glass ceramic restoration through a CAD / CAM process, and no crystallization treatment is required.
[0079] Table 7
[0080]
[0081]
[0082] Example 8 (Melting Method CAD Secondary Crystallization)
[0083] According to the component contents shown in Table 8 below, take the raw material components of the basic glass, and each raw material can be selected from its oxide, carbonate or phosphate, etc., and mix them thoroughly; put the mixed raw materials into a platinum crucible, put the platinum crucible into a furnace for melting, control the melting temperature to 1500°C, and the melting time to 100 minutes to homogenize the glass liquid, and then pour it into cold water to obtain a glass frit; the glass frit is then melted at 1600°C for 80 minutes, and then cast into a mold for molding, and the ceramic block is crystallized at 680°C in a box furnace for 2 hours to obtain a CAD ceramic block. The obtained CAD ceramic block is subjected to a CAD / CAM process, and at the same time, it needs to be crystallized at 830°C for 1 hour to prepare a lithium disilicate glass ceramic restoration.
[0084] Table 8
[0085]
[0086]
[0087] Example 9 (Sintering Press)
[0088] According to the component contents shown in Table 9 below, take the raw material components of the basic glass, and each raw material can be selected from its oxide, carbonate or phosphate, etc., and mix them thoroughly; put the mixed raw materials into a platinum crucible, put the platinum crucible into a furnace for melting, control the melting temperature to 1600°C, and the melting time to 80min, so that the glass liquid is homogenized, and then poured into cold water to obtain a glass frit; the frit is coarsely ground and finely ground to a particle size of D50=10μm, and the ground glass powder is placed in a prepared mold, dry pressed, with a molding pressure of 100MPa, and then isostatically pressed, with a pressure of 200MPa; the blank is sintered in a vacuum atmosphere furnace, sintered at a temperature of 870°C for 1h, and the vacuum degree is controlled at 2000Pa. The obtained press porcelain block can be prepared into a lithium disilicate glass ceramic restoration by a hot die casting process.
[0089] Table 9
[0090] Element Content wt% SiO2 52 Li2O 9 P2O5 5 K2O 3 Al2O3 13.3 ZrO2 1 ZnO 15 Tb4O7 1 BaO 0.5 SrO 0.8 Zirconium Vanadium Yellow 0.2 Dy2O3 0.1 Nd2O3 0.1
[0091] Example 10 (Sintering CAD primary crystallization)
[0092] According to the component contents shown in Table 10 below, take the raw material components of the basic glass, and each raw material can be selected from its oxide, carbonate or phosphate, etc., and mix them thoroughly; put the mixed raw materials into a platinum crucible, put the platinum crucible into a furnace for melting, control the melting temperature to 1480°C, and the melting time to 100min, so that the glass liquid is homogenized, and then poured into cold water to obtain a glass frit; the frit is coarsely ground and finely ground to a particle size of D50=15μm, and the ground glass powder is placed in a prepared mold, dry pressed once, and the pressure is 180MPa; the blank is sintered in a vacuum atmosphere furnace at a temperature of 890°C for 1h, and the vacuum degree is controlled at 2500Pa. The obtained CAD ceramic block can be used to prepare a lithium disilicate glass ceramic restoration through a CAD / CAM process without the need for crystallization treatment.
[0093] Table 10
[0094] Element Content wt% SiO2 58 Li2O 14 P2O5 2.5 K2O 3.6 Al2O3 10.5 ZrO2 0.4 ZnO 9 Tb4O7 0.3 CaO 0.5 MgO 0.2 SrO 0.1 TiO2 0.2 Zirconium praseodymium yellow 0.2 Chrome tin red 0.1 Nd2O3 0.2 Yb2O3 0.1 Tm2O3 0.1
[0095] Comparative Example 1 (Melting Method CAD Secondary Crystallization)
[0096] According to the component contents shown in Table 11 below, take the raw material components of the basic glass, and each raw material can be selected from its oxide, carbonate or phosphate, etc., and mix them thoroughly; put the mixed raw materials into a platinum crucible, put the platinum crucible into a furnace for melting, control the melting temperature to 1630°C, and the melting time to 80 minutes to homogenize the glass liquid, and then pour it into cold water to obtain a glass frit; the glass frit is then melted at 1480°C for 120 minutes, and then cast into a mold for molding, and the ceramic block is crystallized at 630°C in a box furnace for 2 hours to obtain a CAD ceramic block. The obtained CAD ceramic block is subjected to a CAD / CAM process, and at the same time, it needs to be crystallized at 830°C for 1 hour to prepare a lithium disilicate glass ceramic restoration.
[0097] Table 11
[0098] Element Content wt% SiO2 58.7 Li2O 13.3 P2O5 4 K2O 5.7 Al2O3 5 ZrO2 2.5 ZnO 6 Tb4O7 0.8 CaO 1 La2O3 0.5 TiO2 0.5 V2O5 0.3 MoO3 0.5 Pr2O3 0.6 NiO 0.2 Tm2O3 0.2
[0099] In Comparative Example 1, the Al2O3 content wt% is less than 10%, and the ZnO content wt% is less than 9%, both of which are lower than the Al2O3 and ZnO contents wt% in the present invention. The strength and fracture toughness of the samples tested are also lower than the strength and fracture toughness tested by the samples of the present invention. For specific data, please see Table 17.
[0100] Comparative Example 2 (Melting Method CAD Secondary Crystallization)
[0101] According to the component contents shown in Table 12 below, take the raw material components of the basic glass, and each raw material can be selected from its oxide, carbonate or phosphate, etc., and mix them thoroughly; put the mixed raw materials into a platinum crucible, put the platinum crucible into a furnace for melting, control the melting temperature to 1630°C, and the melting time to 80 minutes to homogenize the glass liquid, and then pour it into cold water to obtain a glass frit; the glass frit is then melted at 1480°C for 120 minutes, and then cast into a mold for molding, and the ceramic block is crystallized at 660°C in a box furnace for 2 hours to obtain a CAD ceramic block. The obtained CAD ceramic block is subjected to a CAD / CAM process, and at the same time, it needs to be crystallized at 830°C for 1 hour to prepare a lithium disilicate glass ceramic restoration.
[0102] Table 12
[0103] Element Content wt% SiO2 60.4 Li2O 13.7 ZnO 3.5 K2O 4 Al2O3 11 ZrO2 1 P2O5 4.2 Tb4O7 0.5 V2O5 0.4 Er2O3 0.2 Tm2O3 0.4 Eu2O3 0.7
[0104] In Comparative Example 2, the Al2O3 content wt% is within the range of 10<Al2O3<15% of the present invention, and the ZnO content wt%<9%. The sample contains too much unreacted Al2O3, so after heat treatment at 660°C, uneven crystallization occurs and no product can be formed.
[0105] Comparative Example 3 (Melting Method CAD Secondary Crystallization)
[0106] According to the component contents shown in Table 13 below, take the raw material components of the basic glass, and each raw material can be selected from its oxide, carbonate or phosphate, etc., and mix them thoroughly; put the mixed raw materials into a platinum crucible, put the platinum crucible into a furnace for melting, control the melting temperature to 1500°C, and the melting time to 100 minutes to homogenize the glass liquid, and then pour it into cold water to obtain a glass frit; the glass frit is then melted at 1600°C for 80 minutes, and then cast into a mold for forming, and the ceramic block is crystallized at 640°C in a box furnace for 2 hours to obtain a CAD ceramic block. The obtained CAD ceramic block is subjected to a CAD / CAM process, and at the same time, it needs to be crystallized at 850°C for 1.5 hours to prepare a lithium disilicate glass ceramic restoration.
[0107] Table 13
[0108] Element Content wt% SiO2 57.3 Li2O 13 P2O5 3.5 K2O 4.6 Al2O3 6 ZrO2 1.2 ZnO 10.2 Tb4O7 0.4 CaO 0.2 BaO 0.3 SrO 1 TiO2 0.5 V2O5 0.5 Er2O3 0.5 Dy2O3 0.4 Yb2O3 0.4
[0109] In Comparative Example 3, the wt% content of ZnO is within the range of 9<ZnO<15% of the present invention, and the wt% content of Al2O3 is less than 10%. Too much ZnO in the sample will lead to poor transparency of the sample, and it will soften and deform after heat treatment at 640°C, and cannot form a product.
[0110] Comparative Example 4 (Melting Method CAD Secondary Crystallization)
[0111] According to the component contents shown in Table 14 below, take the raw material components of the basic glass, and each raw material can be selected from its oxide, carbonate or phosphate, etc., and mix them thoroughly; put the mixed raw materials into a platinum crucible, put the platinum crucible into a furnace for melting, control the melting temperature to 1630°C, and the melting time to 80 minutes to homogenize the glass liquid, and then pour it into cold water to obtain a glass frit; the glass frit is then melted at 1480°C for 120 minutes, and then cast into a mold for molding, and the ceramic block is crystallized at 660°C in a box furnace for 2 hours to obtain a CAD ceramic block. The obtained CAD ceramic block is subjected to a CAD / CAM process, and at the same time, it needs to be crystallized at 830°C for 1 hour to prepare a lithium disilicate glass ceramic restoration.
[0112] Table 14
[0113] Element Content wt% SiO2 53.4 Li2O 12.7 ZnO 15.5 K2O 3 Al2O3 11 ZrO2 0.2 P2O5 3.2 Tb4O7 0.3 V2O5 0.2 Er2O3 0.1 Tm2O3 0.2 Eu2O3 0.2
[0114] In Comparative Example 4, the Al2O3 content wt% is within the range of 10<Al2O3<15% of the present invention, and the ZnO content wt%>15%. The ZnO content in the sample is too high, the product is not transparent enough, is easy to soften, is not suitable for application in the dental field, and cannot form a product.
[0115] Comparative Example 5 (Melting Method CAD Secondary Crystallization)
[0116] According to the component contents shown in Table 15 below, take the raw material components of the basic glass, and each raw material can be selected from its oxide, carbonate or phosphate, etc., and mix them thoroughly; put the mixed raw materials into a platinum crucible, put the platinum crucible into a furnace for melting, control the melting temperature to 1650°C, and the melting time to 100 minutes to homogenize the glass liquid, and then pour it into cold water to obtain a glass frit; the glass frit is then melted at 1600°C for 80 minutes, and then cast into a mold for forming, and the ceramic block is crystallized at 640°C in a box furnace for 2 hours to obtain a CAD ceramic block. The obtained CAD ceramic block is subjected to a CAD / CAM process, and at the same time, it needs to be crystallized at 850°C for 1.5 hours to prepare a lithium disilicate glass ceramic restoration.
[0117] Table 15
[0118] Element Content wt% SiO2 52.3 Li2O 12 P2O5 3.5 K2O 3.6 Al2O3 16 ZrO2 0.2 ZnO 10.2 Tb4O7 0.2 CaO 0.2 BaO 0.3 SrO 0.5 TiO2 0.3 V2O5 0.2 Er2O3 0.1 Dy2O3 0.2 Yb2O3 0.2
[0119] In Comparative Example 5, the wt% content of ZnO is within the range of 9<ZnO<15% of the present invention, and the wt% content of Al2O3 is>15%. The viscosity of the molten glass after melting is high, making it difficult to shape, mass produce, and form products.
[0120] Comparative Example 6 (Melting Method CAD Secondary Crystallization)
[0121] According to the component contents shown in Table 16 below, take the raw material components of the basic glass, and each raw material can be selected from its oxide, carbonate or phosphate, etc., and mix them thoroughly; put the mixed raw materials into a platinum crucible, put the platinum crucible into a furnace for melting, control the melting temperature to 1630°C, and the melting time to 80 minutes to homogenize the glass liquid, and then pour it into cold water to obtain a glass frit; the glass frit is then melted at 1480°C for 120 minutes, and then cast into a mold for molding, and the ceramic block is crystallized at 630°C in a box furnace for 2 hours to obtain a CAD ceramic block. The obtained CAD ceramic block is subjected to a CAD / CAM process, and it also needs to be crystallized at 830°C for 1 hour to prepare a lithium disilicate glass ceramic restoration.
[0122] Table 16
[0123] Element Content wt% SiO2 48.2 Li2O 11.3 P2O5 2 K2O 3.7 Al2O3 15.5 ZrO2 0.5 ZnO 16 Tb4O7 0.3 CaO 0.5 La2O3 0.5 TiO2 0.4 V2O5 0.1 MoO3 0.2 Pr2O3 0.3 Dy2O3 0.1 Tm2O3 0.2
[0124] In Comparative Example 6, the Al2O3 content wt%>15%, the ZnO content wt%>15%, both of which are greater than the Al2O3 and ZnO content wt% in the present invention. The SiO2 and Li2O contents in the sample are relatively low, resulting in a low content of the main crystalline phase of lithium disilicate in the product. After crystallization treatment at 630°C, the sample is severely softened, has pores, does not show color, and appears chalky, and cannot form a product.
[0125] Performance Testing
[0126] The properties of the dental restoration materials obtained in the above Examples 1-10 and Comparative Example 1 were tested, and the test results are shown in the following table, wherein the strength and fracture toughness testing methods are to prepare and test the samples in accordance with ISO6872 standard.
[0127] Table 17
[0128] Sample name Strength (MPa) <![CDATA[Fracture toughness (MPa·m 1 / 2 )]]> Example 1 532.47 2.19 Example 2 556.28 1.97 Example 3 565.29 2.15 Example 4 517.44 2.22 Example 5 576.21 1.94 Example 6 518.35 2.34 Example 7 537.41 2.19 Example 8 534.28 1.98 Example 9 553.87 2.07 Example 10 574.33 2.03 Comparative Example 1 412.83 1.74
[0129] Compared with Comparative Example 1, the strength and fracture toughness of Examples 1-10 are significantly increased, and the XRD detection of ZnAl2O4 crystals indicates that the component range of Examples 1-10 can form ZnAl2O4 crystals well and improve the strength and fracture toughness of the product. Comparative Examples 2-6 show that when the wt% content of Al2O3 and ZnO is not within the range of the present invention at the same time, various problems will occur in the product, and the production needs cannot be met, and the product cannot be formed.
Claims
1. A lithium disilicate glass-ceramic containing zinc spinel as a secondary crystalline phase, characterized in that: The method is prepared by simultaneously introducing ZnO and Al2O3, which are necessary for forming the galvanneal secondary crystalline phase, into the basic glass components during the glass melting stage, melting the glass in an air atmosphere, and adopting a casting method or a sintering method. In the obtained product, galvanneal is precipitated as a secondary crystalline phase in the main crystalline phase lithium silicate glass ceramics.
2. The lithium disilicate glass ceramic according to claim 1, characterized in that: The basic glass component includes the following components in percentage by mass:
3. The lithium disilicate glass ceramic according to claim 2, characterized in that: The basic glass component also includes a compound containing Tb ions, and the content of the compound is 0.2-0.5% by mass percentage of Tb4O7.
4. The lithium disilicate glass ceramic according to claim 2, characterized in that: The invention also includes an additive, wherein the additive is selected from at least one of alkaline earth metal oxides, trivalent element oxides, tetravalent element oxides, pentavalent element oxides and hexavalent element oxides, and the content of the additive is 0-12 wt %; The alkaline earth metal oxide is selected from at least one of CaO, BaO, MgO, SrO or a mixture thereof; the oxide of the trivalent element is other than Al2O3 and is selected from at least one of B2O3, Y2O3, La2O3, Bi2O3 or a mixture thereof; the oxide of the tetravalent element is other than SiO2, ZrO2, TiO2 and is selected from at least one of SnO2, TiO2 and GeO2; the oxide of the pentavalent element is selected from at least one of P2O5 and Nb2O5; the oxide of the hexavalent element is selected from at least one of WO3 and MoO3.
5. The lithium disilicate glass ceramic according to claim 2, characterized in that: It also includes a colorant, wherein the colorant is selected from at least one of a yellow colorant, a red colorant, and a gray colorant, and the content thereof is 0-5.5wt%; The yellow colorant is selected from at least one of CeO2, Pr2O3, and V2O5; the red colorant is Er2O3; and the gray colorant is selected from at least one of MnO, NiO, and Nd2O3.
6. The lithium disilicate glass ceramic according to claim 2, characterized in that: It also includes a fluorescent agent, wherein the fluorescent agent includes at least one of oxides, carbonates, nitrates, and phosphates of at least two of the following elements Sm, Dy, Er, Yb, Nd, Tm, and Eu, and the content thereof is 0.1-3wt%; The base glass component also includes no more than 0.01 wt % of Fe ions.
7. The method for preparing the lithium disilicate glass ceramic according to any one of claims 1 to 6, characterized in that: The following steps are involved: According to the formula, basic glass components, additives, colorants and fluorescent agents are selected and mixed evenly, melted and water quenched in an air atmosphere, the quenched glass frit is melted again, and the melted glass liquid is poured into the required mold for molding and heat treatment.
8. The preparation method according to claim 7, characterized in that: The melting temperature is 1450℃-1650℃, and the holding time is 60-120min; The remelting temperature is 1450℃-1650℃, and the holding time is 60-120min; The heat treatment temperature is 500-1100℃.
9. The method for preparing lithium disilicate glass ceramics according to any one of claims 1 to 6, characterized in that: The following steps are involved: According to the formula, basic glass components, additives, colorants and fluorescent agents are selected and mixed evenly, melted and water quenched in an air atmosphere, the water-quenched glass frit is ground into glass powder, and then the glass powder is placed in a mold for pressing and forming, and is obtained after heat treatment.
10. The preparation method according to claim 9, characterized in that: Colorants and / or mixed glass powder with transparency are added to the glass powder as a layer of common powder, which is then put into a mold for pressing.
11. The preparation method according to claim 10, characterized in that: Add at least three layers of common powder.
12. The preparation method according to any one of claims 9 to 11, characterized in that: The melting temperature is 1450℃-1650℃, and the holding time is 60-120min; The average particle size of the ground powder is 1-100um; During pressing, dry pressing is adopted with a molding pressure of 100-260MPa, or dry pressing is first performed with a pressure of 15-100MPa, and then isostatic pressing is performed with a pressure of 100-260MPa; The sintering temperature is 350-1200°C and the vacuum degree is controlled at 100-5000Pa.
13. A dental restoration, characterized in that The lithium disilicate glass ceramic is prepared by using the lithium disilicate glass ceramic described in any one of claims 1 to 6.
14. The dental restoration according to claim 13, characterized in that Compared with the traditional lithium disilicate glass ceramics made of dental restorations, the strength reaches more than 498MPa and the fracture toughness reaches 1.9MPa·m 1 / 2 above.